2022
DOI: 10.1093/mnras/stac3245
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Eddington black hole growth in star-forming molecular clouds and galactic nuclei: can it happen?

Abstract: Formation of supermassive black holes (BHs) remains a theoretical challenge. In many models, especially beginning from stellar relic “seeds,” this requires sustained super-Eddington accretion. While studies have shown BHs can violate the Eddington limit on accretion disk scales given sufficient “fueling” from larger scales, what remains unclear is whether or not BHs can actually capture sufficient gas from their surrounding ISM. We explore this in a suite of multi-physics high-resolution simulations of BH grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 178 publications
0
1
0
Order By: Relevance
“…The gray dashed line shows our best-fit power-law continuum model, where the continuum slope index is α λ = −1.32 ± 0.30. massive BH can power this source if rapid super-Eddington accretion is achieved. The necessity of such intermittent super-Eddington phases has been recently argued in theoretical predictions of early BH assembly (Hu et al 2022;Inayoshi et al 2022a;Shi et al 2023). On the other hand, the same luminosity can also be achieved by a sub-Eddington BH with M BH ; 10 7−8 M e , as long as the nuclear accretion disk settles down to a radiatively efficient state (L bol /L Edd  0.01; see Yuan & Narayan 2014).…”
Section: Continuum Propertiesmentioning
confidence: 98%
“…The gray dashed line shows our best-fit power-law continuum model, where the continuum slope index is α λ = −1.32 ± 0.30. massive BH can power this source if rapid super-Eddington accretion is achieved. The necessity of such intermittent super-Eddington phases has been recently argued in theoretical predictions of early BH assembly (Hu et al 2022;Inayoshi et al 2022a;Shi et al 2023). On the other hand, the same luminosity can also be achieved by a sub-Eddington BH with M BH ; 10 7−8 M e , as long as the nuclear accretion disk settles down to a radiatively efficient state (L bol /L Edd  0.01; see Yuan & Narayan 2014).…”
Section: Continuum Propertiesmentioning
confidence: 98%
“… , where t Sal = κ es c/(4πG) ≈ 45 Myr is the Salpeter time and ò ref is an assumed radiative efficiency (typically 0.1; Inayoshi et al 2020). Thus, to grow to SMBH masses from "seed" masses =10 6 M e (Greene et al 2020) at high redshifts generally requires either accretion well above this naive Eddington limit (Inayoshi et al 2016;Shi et al 2023) or exotic intermediatemass black hole (IMBH) seed formation scenarios like the direct collapse of unfragmented giant molecular clouds (GMCs) to single hypermassive stars (with SMBH masses themselves; Bromm & Loeb 2003), exotic dark matter/new physics processes (Xiao et al 2021), or runaway mergers of stars (Portegies Zwart et al 2004;Shi et al 2021;Rantala et al 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the problems above are explored in Shi et al (2023), where we embedded BH seeds into star-forming GMCs. We found that significant BH accretion can "stochastically" occur if a dense clump (parsec or subparsec scale) formed via turbulence and stellar feedback shocks (Klessen 2000; Mac Low & Klessen 2004;McKee & Ostriker 2007) is sufficiently gravitationally bound and close (subparsec) to the BH and if the gas is sufficiently dense and cold (Inayoshi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations